2014
DOI: 10.1186/1477-7525-12-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Turkish version of the quality of recovery-40 questionnaire

Abstract: BackgroundThe Quality of Recovery-40 questionnaire (QoR-40) is a self-rated questionnaire used to assess the postoperative recovery quality and health status of patients in the early stages following surgery; however, there is no Turkish version of the QoR-40. The aim of this study was to assess the reliability, validity, and responsiveness of the Turkish version of the QoR-40 (QoR-40 T).MethodsAfter the approval of the ethics committee, a total of 137 patients completed the questionnaire during the preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 14 publications
5
45
0
16
Order By: Relevance
“…(14) The QoR-40 responsiveness in other cultures was investigated between measures of pre-and postoperative periods, obtaining similar results -a moderate to significant effect. (15)(16)(17)(18) When investigating long term responsiveness, measurement between pre-and postoperative (90 days) of patients submitted to neurological surgeries, Australian researchers identified the QoR-40 good ability in detecting recovery changes (SRM>0.80). (19) The recovery monitoring over time showed that in the second return (about seven months after surgery), the QoR-40 scores were higher than the ones found in the preoperative period, characterizing an improvement in health status identified by the instrument.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(14) The QoR-40 responsiveness in other cultures was investigated between measures of pre-and postoperative periods, obtaining similar results -a moderate to significant effect. (15)(16)(17)(18) When investigating long term responsiveness, measurement between pre-and postoperative (90 days) of patients submitted to neurological surgeries, Australian researchers identified the QoR-40 good ability in detecting recovery changes (SRM>0.80). (19) The recovery monitoring over time showed that in the second return (about seven months after surgery), the QoR-40 scores were higher than the ones found in the preoperative period, characterizing an improvement in health status identified by the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, the internal consistence of the total was 0.93, with a variation in dimensions of 0.82 to 0.92; in Iran, alpha was 0.89 for the total, and 0.89 to 0.93 for dimensions; in Japan, it was 0.91 for the total and 0.74 to 0.88 for dimensions. (3,16,18) Despite the questionnaire's acceptable reliability, items that might have interfered negatively in the results were identified. Items that investigate skills of communication and self-care did not receive variability of responses (preoperative and second return), i.e., all patients pointed to the best response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the investigator applied the questionnaire. The Turkish version of QoR-40 has been tested for validity and reliability (12). Cronbach-α values were suitable for our study group.…”
Section: Discussionmentioning
confidence: 99%
“…The Quality of Recovery-40 (QoR-40) scale evaluates the quality of recovery postoperatively, and the Turkish form has been shown to be valid and reliable (11,12). Studies investigating the quality of recovery after general and spinal anaesthesia in emergency caesarean deliveries are scarce.…”
Section: Introductionmentioning
confidence: 99%